2022
DOI: 10.3390/ani12040426
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Role of Vascular and Lymphatic Endothelial Cells in Filarial Infections

Abstract: The embryonic stage of filarial nematodes, or microfilariae (Mf), shows daily and seasonal periodicity that requires their migration through blood vessels into the lungs, where they are sequestered when not circulating in the peripheral blood. Therefore, Mf and the host endothelium are likely in a permanent state of hide and seek. Interestingly, filarial nematodes co-cultured in media with a murine endothelial cell line survive eight times longer than those cultured in media alone. This suggests that the endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Cultures of lymphatic endothelial cells in the presence of live worms or Wuchereria bancrofti antigens activated lymphatic vessel remodeling, causing cell proliferation and cell differentiation. These events have been linked to processes that facilitate vascular irrigation in damaged tissues [33]. However, some authors have shown that angiogenesis and/or lymphangiogenesis can be induced by various factors derived from adult worm-activated monocytes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of lymphatic endothelial cells in the presence of live worms or Wuchereria bancrofti antigens activated lymphatic vessel remodeling, causing cell proliferation and cell differentiation. These events have been linked to processes that facilitate vascular irrigation in damaged tissues [33]. However, some authors have shown that angiogenesis and/or lymphangiogenesis can be induced by various factors derived from adult worm-activated monocytes [34][35][36].…”
Section: Discussionmentioning
confidence: 99%